KNOWLEDGE, ATTITUDES, AND PRACTICES ON ELECTRONIC WASTE MANAGEMENT AMONG MAKERERE UNIVERSITY STUDENTS, KAMPALA, UGANDA: A CROSS-SECTIONAL STUDY. - JABIM, PHILLIAM; MUSOKE, DAVID (Student's Journal of Health Research Africa, 2024)
Background The need for electronics such as laptops and phones are on the rise, especially in academic institutions including universities. These electronics are required for day-to-day activities such as lectures and communication. As time goes by, these electronics may no longer be required by the original user hence resulting in high volumes of electronic waste (e-waste). This generation of e-waste requires proper management to protect human health and the environment. This study therefore assessed the knowledge, attitudes, and practices on e-waste management among Makerere University students in Kampala, Uganda. Methods A cross-sectional descriptive study using a structured questionnaire to collect quantitative data was conducted among 336 Makerere University students. Collected data was analysed at a univariate level in STATA 14 software to assess knowledge, attitudes, and practices on e-waste management among the students. Results The majority of participants 267 (79.5%) were aged between 20-25 years, and more than half 179 (53.3%) were males. Most participants 153 (45.5%) had low knowledge levels on e-waste management, though the majority 180 (53.6%) knew what e-waste is. The majority of participants 275 (81.8%) had positive attitudes toward e-waste management, and nearly all 319 (94.9%) agreed that e-waste should not be disposed of with general waste. Mobile phones 223 (42.6%) were the most disposed of e-waste. Many students 125 (35.3%) discarded e-waste by selling as second-hand. Conclusion There was low knowledge, positive attitudes, and poor practices towards e-waste management among the university students. Recommendation There is a need for various stakeholders to enhance knowledge among students regarding the effects of poor e-waste management on humans and the environment to improve management practices. For example, university administrations can organise campaigns, webinars, and seminars that focus on proper e-waste management including disposal practices and effects on human health and the environment.